Answer:
y = 2x-4
all the equations are the same as the slope-intercept form is the same for all the equations
Explanation:
slope-intercept form:
2x-3 = y+1
i) move y to the left-hand side and change its sign
-y+2x-3 = 1
ii) move 2x-3 to the right-hand side and change its sign
-y = 1-2x+3
iii) add the numbers
-y = (1+3)-2x
-y = 4-2x
iv) change the signs on both sides of the equation
y = -4+2x
v) use the commutative property to reorder the terms
( commutative property: the number on which we operate can be moved or swapped from their position without making any difference to the answers )
y = 2x-4